Money Illusion and Balance-of-Payments Adjustment - Murphy, J. C.; Das, S. K. (Journal of Political Economy, 1976)
Money illusion, taking the form of lagged price perceptions and viewed in a competitive general equilibrium context, is shown in this paper to reduce the change in a country's balance of payments attributable to a devaluation of given size. Illusion's effect on adjustment is also shown to be probably greater under flexible than under fixed exchange-rate arrangements. The results contrast with a view that illusion, in disguising real-income changes, facilitates the elimination of a balance-of-payments deficit.